Processed pseudogenes of human endogenous retroviruses generated by LINEs: their integration, stability, and distribution - Pavlícek, Adam; Paces, Jan; Elleder, Daniel; Hejnar, Jirí (Genome research, 2002)
We report here the presence of numerous processed pseudogenes derived from the W family of endogenous retroviruses in the human genome. These pseudogenes are structurally colinear with the retroviral mRNA followed by a poly(A) tail. Our analysis of insertion sites of HERV-W processed pseudogenes shows a strong preference for the insertion motif of long interspersed nuclear element (LINE) retrotransposons. The genomic distribution, stability during evolution, and frequent truncations at the 5' end resemble those of the pseudogenes generated by LINEs. We therefore suggest that HERV-W processed pseudogenes arose by multiple and independent LINE-mediated retrotransposition of retroviral mRNA. These data document that the majority of HERV-W copies are actually nontranscribed promoterless pseudogenes. The current search for HERV-Ws associated with several human diseases should concentrate on a small subset of transcriptionally competent elements.
Keywords: integrace viru; Long Interspersed Nucleotide Elements; lidé; Base Sequence; Genome, Human; Endogenous Retroviruses; GC Rich Sequence; endogenní retroviry; RNA Stability; GC bohatá sekvence; Humans; pseudogeny; Virus Integration; RNA, Viral; genom lidský; fylogeneze; dlouhé rozptýlené jaderné elementy; RNA Processing, Post-Transcriptional; molekulární sekvence - údaje; Molecular Sequence Data; stabilita RNA; Pseudogenes; Phylogeny; RNA virová; sekvence nukleotidů; posttranskripční úpravy RNA